Production of a β-d-glucan-rich extract from Shiitake mushrooms (Lentinula edodes) by an extraction/microfiltration/reverse osmosis (nanofiltration) process. (January 2019) - Morales, Diego; Smiderle, Fhernanda Ribeiro; Piris, Adriana Jimenez; Soler-Rivas, Cristina; Prodanov, Marin
Abstract: A pilot-scale process combining extraction of Shiitake mushroom ( Lentinula edodes ) powder in water (98 °C, 1 h), cross-flow microfiltration and reverse osmosis (nanofiltration) was performed to obtain β-glucan-rich extracts. Suspensions (45–80 L) obtained after 3 extractions were clarified by microfiltration reducing their turbidity to <1 NTU. Membrane flux was completely recovered after filtration. One of the clarified extracts was concentrated (to 6–7 L) by reverse osmosis (Nanomax95) and the other two by nanofiltration (Nanomax50 and ALNF99-2517). Different physicochemical parameters (permeate flux, total soluble substances, total suspended particles and electrical conductivity) were monitored during filtration and the bioactive compounds present in the obtained fractions (β-glucans, total carbohydrates, chitins, eritadenine, lenthionine, ergosterol) were analyzed. The more adequate membrane for Shiitake extract concentration was Nanomax50 because it showed higher filtration flux and higher values of bioactive compounds in the obtained extract than the extracts obtained with the other two membranes. Industrial relevance: This work describes a pilot-scale procedure for obtaining β-d -glucan-rich extracts from Lentinula edodes (Shiitake mushrooms). The extracts might be used in novel functional foods due to their high content in hypocholesterolemic compounds. The process combines extraction with boiling water, cross-flow membrane clarification and reverse osmosis/nanofiltration concentration of β-d -glucans. The procedure is scalable to industrial level. Highlights: Hypocholesterolemic β-d -glucans rich extracts (13–18%) were obtained from L. edodes . Extracts were clarified by cross-flow membrane microfiltration. Clarified extracts were concentrated by reverse osmosis/nanofiltration. Nanomax50 nanofiltration membrane gave the highest β-d -glucans enrichment. Other hypocholesterolemic compounds such as eritadenine were extracted.